Factors associated with persistent colonisation with methicillin-resistant Staphylococcus aureus. Issue 7 (21st February 2017) - CLUZET, V. C.; GERBER, J. S.; NACHAMKIN, I.; COFFIN, S. E.; DAVIS, M. F.; JULIAN, K. G.; ZAOUTIS, T. E.; METLAY, J. P.; LINKIN, D. R.; TOLOMEO, P.; WISE, J. A.; BILKER, W. B.; et al.
SUMMARY: We conducted a prospective cohort study between 1 January 2010 and 31 December 2012 at five adult and paediatric academic medical centres to identify factors associated with persistent methicillin-resistant Staphylococcus aureus (MRSA) colonisation. Adults and children presenting to ambulatory settings with a MRSA skin and soft tissue infection (i.e. index cases), along with household members, performed self-sampling for MRSA colonisation every 2 weeks for 6 months. Clearance of colonisation was defined as two consecutive negative sampling periods. Subjects without clearance by the end of the study were considered persistently colonised and compared with those who cleared colonisation. Of 243 index cases, 48 (19·8%) had persistent colonisation and 110 (45·3%) cleared colonisation without recurrence. Persistent colonisation was associated with white race (odds ratio (OR), 4·90; 95% confidence interval (CI), 1·38–17·40), prior MRSA infection (OR 3·59; 95% CI 1·05–12·35), colonisation of multiple sites (OR 32·7; 95% CI 6·7–159·3). Conversely, subjects with persistent colonisation were less likely to have been treated with clindamycin (OR 0·28; 95% CI 0·08–0·99). Colonisation at multiple sites is a risk factor for persistent colonisation and may require more targeted decolonisation efforts. The specific effect of clindamycin on MRSA colonisation needs to be elucidated.